The Effectiveness Of Peer-Mediated Sandplay to Promote Social interactions among children with Autism (Journal of the College of Basic Education, 2020)
This study aimed at assessing whether playing with typically developing peers increased numbers of Social interactions in children with Autism Disorder (ASD). A version of a sandplay intervention previously investigated by Lu, Petersen, Lacroix, and Rousseau (2010), and modified to include peer-mediated play was used. The intervention explored the effects of sandplay with typically developing peers on engagement in social interactions by children with ASD. A multiple-case intervention design was used with three children with ASD with varying degrees of severity in functioning. While the number of social interactions among the children did increase from baseline with the introduction of the peer-mediated sandplay intervention. While the results of the intervention are inconclusive, these results necessitate further investigation into this method of intervention for children with autism disorder, specifically with regard to ASD severity. Theoretical and treatment implications are offered, as well as directions for future research